(untitled) (Revista Latino-Americana de Enfermagem, 2023)
Objective: to develop and validate the content of a serious game on the safe management of intravenous medications in pediatrics. Method: methodological study for the development and content validation of an educational technology. The cases and challenges of the serious game were developed based on a literature review and validated by 11 nurses with training and experience in the area. Content validity and agreement indices were adopted to analyze agreement and internal consistency (minimum of 0.8). Results: the content is based on the main antibiotics used in the clinical management of infections in hospitalized children and patient safety. Absolute agreement was obtained in 60 of the 61 items evaluated, and the minimum obtained was 0.82 in the content validation index and 0.80 in agreement. Adjustments were suggested by experts in the response statement for a specific case and implemented to improve the quality of the technology content. Conclusion: the content of the serious game Nurseped was validated by nurse experts in child health regarding clinical cases, question statements and multiple-choice answers, in addition to feedback that presents the user with an evidence-based answer after getting the challenge right or wrong.